Lgr5 is a marker for fetal mammary stem cells, but is not essential for stem cell activity or tumorigenesis - Christy L. Trejo (Nature Portfolio, 2017)
Stem cells: protein not needed for stem cell activity in mammary gland A protein considered necessary for mammary stem cell activity turns out to be dispensable. What’s more, it’s not required for tumor development either. Geoffrey Wahl, Christy Trejo, and colleagues from the Salk Institute for Biological Studies in La Jolla, CA, USA, investigated whether the expression of a protein called Lgr5 denotes mammary stem cells and whether it’s truly needed for the cells to be capable of giving rise to two cell lineages—a subject of active debate among researchers. Wahl’s team showed that mouse fetal mammary stem cells expressing Lgr5 had this dual-lineage capacity; their counterparts in the adult mouse did not. Yet, even though Lgr5 expression marks a population of fetal mammary stem cells, the protein is not required for stem cell activity or for tumors to form in a mouse model of breast cancer.